Annual Plan 2012-13 Volume - I General Government of Andhra Pradesh - Planning Commission (Planning Commission, 2012)
Endowed with abundant natural resources - fertile land and highly conducive agro-climatic conditions, Andhra Pradesh State is blessed wish river major systems like the Godavari, Krishna, Pennar, Vamsadhara and 36 other rivulets. The State, with a total geographical area of 275.04 lakh hectares accounts for 8.37% of the Country's area stands 4th largest in the country and enjoys several competitive socio-economic advantages. The State, situated in a tropical region stands as the 2nd longest coastline in the country with a length of 974 km. With 63,814 Sq.Kms of Forest area and accounting for 23.2% the total geographical area, Andhra Pradesh has a variety of physiographic features ranging from high hills, undulating plains to a coastal deltaic environment.
Government of Andhra Pradesh, Planning Department